Review of modeling tool‒rock frictional contact with a blunt PDC cutter - Yaneng Zhou; George Z. Voyiadjis (Journal of Intelligent Construction)
The mechanisms of tool‒rock frictional contact are reviewed, with a focus on recent advances in numerical modeling. An idealized problem is defined for tool‒rock frictional contact with a rigid blunt tool sliding on the surface of a half-space. The governing dimensionless parameters are summarized for rocks characterized by various rock material models. For elastoplastic rock, the mechanism of frictional contact is governed primarily by an elastoplastic parameter η, which contrasts a characteristic elastic stress with a yield strength. For poroelastoplastic rocks, the mechanism is controlled by both η and λ, where λ is a dimensionless parameter representing the ratio between a geometrical length scale and a characteristic dimension with pore pressure perturbation. For quasibrittle rocks with induced isotropic damage, the mechanism is controlled by both η and ξ, where ξ is a dimensionless brittleness number that contrasts a geometrical length scale with a material length scale. For anisotropic damage, the mechanism is governed by η, ξ, and ζ, where ζ is the damage coefficient that controls the ratio of damage in different directions. The influence of these governing dimensionless parameters on the dimensionless average contact stress Π~ is summarized in different regimes.